2009
DOI: 10.1093/brain/awp219
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin-induced neurotoxicity: changes in axonal excitability precede development of neuropathy

Abstract: Administration of oxaliplatin, a platinum-based chemotherapy used extensively in the treatment of colorectal cancer, is complicated by prominent dose-limiting neurotoxicity. Acute neurotoxicity develops following oxaliplatin infusion and resolves within days, while chronic neuropathy develops progressively with higher cumulative doses. To investigate the pathophysiology of oxaliplatin-induced neurotoxicity and neuropathy, clinical grading scales, nerve conduction studies and a total of 905 axonal excitability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
175
4
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(201 citation statements)
references
References 53 publications
12
175
4
10
Order By: Relevance
“…Symptom severity scores and clinical and nerve function parameters were correlated within individual patients with Spearman rank correlation coefficients. To determine the relationship between excitability measures during oxaliplatin treatment and follow-up measures, a sum score of composite excitability was determined by combining the measures refractoriness, superexcitability, and threshold electrotonus [8,15] and was correlated within individual patients' clinical neurotoxicity scores (TNSc and TNSr). To compare assessments across multiple time points (pre-oxaliplatin, post-oxaliplatin, and follow-up), assessments were paired and compared within patients using Wilcoxon signed rank tests (two-tailed).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Symptom severity scores and clinical and nerve function parameters were correlated within individual patients with Spearman rank correlation coefficients. To determine the relationship between excitability measures during oxaliplatin treatment and follow-up measures, a sum score of composite excitability was determined by combining the measures refractoriness, superexcitability, and threshold electrotonus [8,15] and was correlated within individual patients' clinical neurotoxicity scores (TNSc and TNSr). To compare assessments across multiple time points (pre-oxaliplatin, post-oxaliplatin, and follow-up), assessments were paired and compared within patients using Wilcoxon signed rank tests (two-tailed).…”
Section: Discussionmentioning
confidence: 99%
“…To compare assessments across multiple time points (pre-oxaliplatin, post-oxaliplatin, and follow-up), assessments were paired and compared within patients using Wilcoxon signed rank tests (two-tailed). Results are expressed as the mean Ϯ standard error of the mean (SEM) or, alternatively, as the median and interquartile range (IQR) as a measure of variability [15]. Significance was defined as p Յ .05.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cold hypersensitivity is a typical feature observed in acute oxaliplatin-induced neurotoxicity. It has been shown that acute modulation of sodium channels influences the severity of oxaliplatin-induced neurotoxicity [39,40]. The involvement of sodium channels is also reported in paclitaxel-induced neuropathic pain, where low doses of tetrodotoxin result able to prevent pain induced by taxane [41].…”
Section: Introductionmentioning
confidence: 97%